Application of The Jigsaw Learning Model to Improve Social Skill in Long Jump Learning - Naufal Putra Ramadhan; Anin Rukmana; Encep Sudirjo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research examines general problems related to low social skills. During their education, students often face a series of challenges, one of which is a lack of social skills. This deficiency is evident in students’ inability to interact effectively with both peers and teachers during the learning process, which hinders their ability to fully benefit from the educational experience. This research involved 20 Students in class V at elementary school Sukamaju Rancaekek, Bandung Regency,, with 10 male students and 10 female students. This research uses observation as the data collection method. Descriptive quantitative, and Qualitative data analysis techniques were used. The success indicator for this research is a 90% percentage of students social skills. The research results show that applying the jigsaw learning model in long jump learning can improve the social skills of Students in class V at elementary school Sukamaju Rancaekek, Bandung Regency,. The pre-cycle data observations resulted in 58%. The growth rate of social skills in cycle I reached 84.4%, while in cycle II it reached 93%. The results of cycle II revealed that students achieved a social skills success indicator of 90%, and the research was halted. Thus, it can be concluded from this research that the application of jigsaw-type cooperative learning in long jump can promote social skills in students in class V at elementary school Sukamaju Rancaekek, Bandung Regency.